STUDI PENENTUAN LOKASI UNTUK PENGEMBANGAN BUDIDAYA RUMPUT LAUT DI WILAYAH PERAIRAN TELUK SALEH, SUMBAWA, NTB - Suniada, Komang Iwan; Indriyawan, Muji Wasis (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 8 No 1 (2014), 2014)
This study was carried out to support the strategic plan of the Ministry of Marine Affairs and Fisheries of Republic of Indonesia that seeks to increase fisheries production through the aquaculture, especially by developing seaweed cultivation around Sumbawa regency. Objective of this study is providing information of potential area for seaweed cultivation around Teluk Saleh water territory, Sumbawa Regency, Nusa Tenggara Barat. Remote sensing data (Terra/Aqua MODIS and Landsat satellite image), field survey data and secondary data were used for this study. Remote sensing data were used to produce Sea Surface Temperature, Chlorophylla information and mapping of bottom substrate, field survey data provided nitrate, phosphate, salinity, pH, DO, TDS, flow velocity, water transparency while secondary data was used to provide bathymetry information. Geographical Information System software was used to analyze this study by using overlay technique for all parameter, which had previously been weighted and scored based on the criteria of aquatic habitat suitability for seaweed cultivation. Higher scoreindicates that the areamoresuitableforseaweed cultivation activities. The results showedthat thepotential areasuitablefor seaweed cultivation activitiesaround Teluk Saleh water territory, Sumbawa Regency, Nusa Tenggara Barat is about 25.532,57 Ha.
Keywords: seaweed cultivation; remote sensing data; Geographic Information system